2022
DOI: 10.3390/su14063253
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Solar–Wind Complementarity Assessment in the Province of Kalinga-Apayao, Philippines Using Canonical Correlation Analysis

Abstract: Increased utilization of renewable energy (RE) resources is critical in achieving key climate goals by 2050. The intermittent nature of RE, especially solar and wind, however, poses reliability concerns to the utility grid. One way to address this problem is to harmonize the RE resources using spatio-temporal complementarity analysis. Two RE resources are said to be complementary if the lack of one is balanced by the abundance of the other, and vice versa. In this work, solar–wind complementarity was analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Dynamic time warping distance (DTW) is suitable for measuring the similarity of source charge time series in both numerical and morphological aspects [16,17]. In [18,19], a quantitative evaluation method for source load timing matching that considers the output fluctuation of renewable energy was proposed. However, currently, for renewable energy combined with energy storage power generation systems, the analysis focuses on the correlation characteristics of renewable energy output and load, whereas the temporal correlation of SGLS requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic time warping distance (DTW) is suitable for measuring the similarity of source charge time series in both numerical and morphological aspects [16,17]. In [18,19], a quantitative evaluation method for source load timing matching that considers the output fluctuation of renewable energy was proposed. However, currently, for renewable energy combined with energy storage power generation systems, the analysis focuses on the correlation characteristics of renewable energy output and load, whereas the temporal correlation of SGLS requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that high-frequency variations of the two resources mostly appear random with no correlation, while longer cycles show a stronger positive or negative correlation to each other. Studies have also proven that RES have high spatial complementarity as their separation distances between sites increase [44], [47], [53], [58].…”
Section: Generation Complementaritymentioning
confidence: 99%
“…Although geographical diversity has been explored and implemented through inter-regional connections moving surplus energy from one network to another, this option must be redesigned through spatial complementarity analysis for intermittent RES [48], [49]. Spatio-temporal complementarity considers both the temporal and spatial correlation and identifies the best complementary relationship [51], [58].…”
Section: Generation Complementaritymentioning
confidence: 99%
See 1 more Smart Citation